Static Analysis 19th International Symposium, SAS 2012, Deauville, France, September 11-13, 2012. Proceedings - Mine, Antoine; Schmidt, David (Programming and Software Engineering,, 2012)
This book constitutes the thoroughly refereed proceedings of the 19th International Symposium on Static Analysis, SAS 2012, held in Deauville, France, in September 2012. The 25 revised full papers presented together with 4 invited talks were selected from 62 submissions. The papers address all aspects of static analysis, including abstract domains, abstract interpretation, abstract testing, bug detection, data flow analysis, model checking, new applications, program transformation, program verification, security analysis, theoretical frameworks, and type checking.